PENGARUH KEDISIPLINAN MENJALANKAN SOP ALUR DINAS TERHADAP KINERJA MASINIS UPT CREW KA KERTAPATI PT KERETA API INDONESIA (PERSERO) DIVISI REGIONAL III PALEMBANG - Chandra, Chandra (Fakultas Ekonomi Universitas IBA, 2018)
This research is aimed to know the influence of discipline in running the SOP of the departmental flow to Performance Engineering UPT Crew KA Kertapati PT. Kereta Api Indonesia (Persero) Divre III Palembang. In this case the sample withdrawal using Boring Sampling method with the population of UPT Crew KA Kertapati as many as 78 people. From the results of the questionnaire, processed using SPSS for Windows version 20 by using simple linear regression method, uju hypothesis (t test), and correlation coefficient. Based on the analysis results obtained value coefficient (R) of 0.433 indicates that there is a strong relationship between the two variables. While on hypothesis (t test) get t value equal to 4,185 t table value sebesat 1,992, and significance value 0,000, then t arithmetic > t table and significance value <0,05, which means Ho rejected H1 accepted, that there is influence of Discipline In Running SOP Flow of Service to Performance. Can also be seen from the value of regression coefficient (R2) of 0.187 that the percentage contribution of variable Discipline In Running SOP Flow Service to variable Performance of 18.7% or variations of variables Discipline In Running SOP Flow Office used to explain the amount of 18.7% Performance variables. While the remaining 81.3% (100% -18.7%) influenced by other variables.